2016
DOI: 10.3109/07420528.2016.1171232
|View full text |Cite
|
Sign up to set email alerts
|

Is problematic mobile phone use explained by chronotype and personality?

Abstract: In this study, the relationships among problematic mobile phone use, age, gender, personality and chronotype of Turkish university students were examined. The study included 902 university students (73% female, 27% male) and their participation in the study was anonymous and voluntary. Data were collected from each participant by assessing a demographic questionnaire, Composite Scale of Morningness (CSM) as a measure of chronotype, the Big Five Inventory (BIG-5) for personality assessment and Mobile Phone Prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 56 publications
5
34
0
Order By: Relevance
“…Mobile phone use for calling and texting after lights out was associated with sleep disturbances (short sleep duration, subjective poor sleep quality, excessive daytime sleepiness, and insomnia symptoms) [11]. Results showed that Composite Scale of Morningness (as a measure of chronotype) scores were the best predictor for problematic mobile phone usage, and as a consequence, evening-oriented university students scored higher on the Mobile Phone Problem Usage Scale [12]. The sleep quality worsened with an increasing level of excessive mobile phone use [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phone use for calling and texting after lights out was associated with sleep disturbances (short sleep duration, subjective poor sleep quality, excessive daytime sleepiness, and insomnia symptoms) [11]. Results showed that Composite Scale of Morningness (as a measure of chronotype) scores were the best predictor for problematic mobile phone usage, and as a consequence, evening-oriented university students scored higher on the Mobile Phone Problem Usage Scale [12]. The sleep quality worsened with an increasing level of excessive mobile phone use [13].…”
Section: Introductionmentioning
confidence: 99%
“…e second findings determine that morning types tend to use online or desktop omnichannel more as compared to evening types. Previous research studies suggest that morning types have more focus on detail information and are less risk takers [25,27,43]. erefore, they may choose desktop channels as best source to make buying decisions.…”
Section: Discussionmentioning
confidence: 99%
“…e patterns of mobile usage among evening and morning types are different from each other. Demirhan et al [43] reported that evening types are more technology oriented and they are more prone to mobile phone usage. In contrast, morning types have more focus on traditional media and are less inclined towards the latest technology [44].…”
Section: Research Hypothesesmentioning
confidence: 99%
“…It has also been related to different psychopathological entities, among which are tactile or visual and alterations in mood and behavior. In a study conducted in 256 individuals, aged 18 to 40 years, an increase in the tendency to impulsive behavior was observed [12]; in a study conducted in 1236 individuals with mobile phone dependence, the degree of anxiety measured by the Zung scale was greater than in a control group with a risk of 10.1% [20]. Alterations have been observed in the volume of gray matter in the right upper frontal gyrus and talamus, as well as less integrity of the white matter in the hippocampus, structures closely related to the limbic system [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, its reliability and internal consistency were analyzed in a sample of 1126 individuals aged 16-65 years, allowing the establishment of four categories of mobile phone use: casual use, regular use, people at risk, and problematic use, with predictive factors such as age, sex, educational level, and time of daily use [19]. This test has also been used in a population of 902 university students in Turkey [20], 1132 students aged 12-18 in Spain, and several countries in Latin America [21], in 412 Swiss teenagers [22], in 1529 adolescents aged 11-18 years in England using the Spanish version [23], in 468 university students in China [24] in 456 adolescents from several European countries, with a Cronbach's alpha of 0.85 and Kendall's Tau of 0.80 [25] and a multinational population of patients from southern Europe, South America, Mesoamerica, India and Pakistan, without finding differences between regions in terms of the psychometric analysis of the reliability of this test [26]. Finally, MMPUS was also used in a sample of 100 university students in Wyoming, United States; a relationship between the high leves of nomophobia and family history of alcoholism was found, which is a fact that has not yet been studied [27].…”
Section: Introductionmentioning
confidence: 99%